Implementation Model of Job Rotation and Job Training in Enhancing Employee Performance Through Job Satisfaction as an Intervening Variable - Dewi Cahyaningrum; Siti Sumiati (International Journal of Economics and Management Sciences, 2024)
This research aims to analyze the influence of Job Rotation and Job Training on Employee Performance through Job Satisfaction. The unit of analysis for this study is PT BPR Arto Moro Semarang. This research is a causal-comparative type, with a sample size of 74 respondents collected through a questionnaire. The sampling method used is non-probability sampling with purposive sampling. The analysis tool employed in this study is Structural Equation Modeling (SEM) using the SmartPLS (Partial Least Square) version 4 application. The results of this study indicate a significant positive influence of Job Rotation on Job Satisfaction, Job Training on Job Satisfaction, and Job Rotation on Employee Performance. However, it does not show a significant impact of Job Satisfaction on Employee Performance and Job Training on Employee Performance at PT BPR Arto Moro.